2020
DOI: 10.1073/pnas.1919753117
|View full text |Cite
|
Sign up to set email alerts
|

Signature of a pair of Majorana zero modes in superconducting gold surface states

Abstract: Under certain conditions, a fermion in a superconductor can separate in space into two parts known as Majorana zero modes, which are immune to decoherence from local noise sources and are attractive building blocks for quantum computers. Promising experimental progress has been made to demonstrate Majorana zero modes in materials with strong spin-orbit coupling proximity coupled to superconductors. Here we show direct evidence of the split Majorana pair in a new material platform utilizing the two-dimensional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(66 citation statements)
references
References 57 publications
(86 reference statements)
3
62
0
Order By: Relevance
“…(34) gradually narrows and diverges, and flips sign as the tuning parameters M = (J, T ) cross the critical point M c , as that described in Eqs. ( 13) and (14). Numerically, we extract critical exponents…”
Section: A Correlation Function and Fidelity Susceptibility For Periodically Driven Kitaev Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(34) gradually narrows and diverges, and flips sign as the tuning parameters M = (J, T ) cross the critical point M c , as that described in Eqs. ( 13) and (14). Numerically, we extract critical exponents…”
Section: A Correlation Function and Fidelity Susceptibility For Periodically Driven Kitaev Modelmentioning
confidence: 99%
“…In addition to representing solid-state realizations of the elusive Majorana fermion in particle physics [4], their nonabelian exchange statistics could be exploited to robustly encode quantum information via braiding schemes [5][6][7]. In recent years, preliminary experimental evidence for their existence [8][9][10][11][12][13][14][15] and notable progress in devising topological quantum computation protocols [16][17][18] fostered an intensive investigation of systems hosting MMs, such as the zerodimensional (0D) edge state at the end of one-dimensional (1D) topological superconductors [19], and the 1D edge state at the boundaries of two-dimensional (2D) topological superconductors [20][21][22]. If time-reversal symmetry (TRS) is present, as in the prototypical Kitaev model on a honeycomb lattice [20], MMs are immobile (nondispersive).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the different velocities and superconducting gaps in each of the pockets, the superconducting coherence lengths will be different in each case, thus enabling the existence of a region with a single Majorana at each end. Such a scenario may help to understand the topological phase diagram of proximitized Rashba states in gold nanowires found in a recent study 28 , 31 . This largely expands the spectrum of material platforms for realization of our proposal, which is a testimony to its great versatility.…”
Section: Discussionmentioning
confidence: 71%
“…So far, Majorana particles remained enigmatic entities, but recently, research groups claimed to have observed "signatures" of these exotic objects (Zhang et al, 2018;Manna et al, 2020). The publication by Zhang et al in Nature was heralded as the "third step" in a Majorana trilogy: from the prediction by Ettore Majorana in 1937, via the group's disappointed first efforts at confirmation, up to the final publication, presented as "definite proof" of the particle's existence.…”
Section: A First Case History: the Majorana Particlementioning
confidence: 99%